2003
DOI: 10.1111/j.1750-3639.2003.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Tumors of Childhood and Infancy. An Update and Literature Review.

Abstract: Meningeal derived tumors of the first 2 decades of life are often diagnostically challenging due to the wide morphologic spectrum encountered and the rarity of most individual entities. The 2 most common patterns include the dural/leptomeningeal‐based mass and neoplastic meningitis. Both primary and secondary meningeal presentations may occur, either early or late in the course of various meningothelial, mesenchymal, embryonal, glial, hematopoietic, histiocytic, melanocytic, and inflammatory tumors. As in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 218 publications
(337 reference statements)
1
66
1
6
Order By: Relevance
“…Children with meningiomas present late in the first decade of life or early in the second [4, 7, 8]. The median age at presentation in this series was 13 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with meningiomas present late in the first decade of life or early in the second [4, 7, 8]. The median age at presentation in this series was 13 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Modan et al[ 6] studied 11,000 children who had been irradiated for tinea capitis and found a fourfold increased risk of meningioma. The prevalence of NF-2 in pediatric patients with meningioma has been shown to be 25–40% [1, 2,7,8,9,10]. Patients with spontaneously arising meningiomas appear to have tumors distinct from those with radiation-induced meningiomas or those associated with NF-2, in that those patients with spontaneously arising meningiomas were younger at the time of diagnosis, were more likely to be female, and had tumors that were more likely to recur and to be malignant.…”
Section: Discussionmentioning
confidence: 99%
“…They comprise only 0.4–4.1% of all pediatric age tumors and only 1.5–1.8% of all intracranial neoplasms in children [1]. In the literature, large series of pediatric meningiomas are uncommon and only a few studies have attempted to analyze the characteristics of these neoplasms in children and the biological differences in comparison to the adult counterparts [1,2,3,4]. We retrospectively analyzed the clinical, pathological and management profile of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Meningiomaların büyük bölümü araknoid villuslardan ve kraniyospinal boşluktaki araknoid membrandaki dağınık gruplar halinde bulunan meningotelyal (araknoidal) hücrelerden kaynaklanır. Çok azı ise dural fibroblastlar, koroid pleksus ve kranyal sinirlerin çev-resindeki araknoidden gelişir (8). Tüm intrakraniyal tümörlerin yaklaşık %13 -26'sını oluştururlar.…”
Section: Introductionunclassified